Medkulturni dialog v EU - Vidmar, Ksenija H. (Družboslovne razprave, 2009)
The article analyses implementation of the European Year of Intercultural Dialogue project in Slovenia. Intercultural dialogue is defined as a key factor in the reconstitution of European society and the reconceptualisation of the notions of European identity and citizenship in the contexts of globalisation and EU enlargements. The study includes an analysis of events organised under the umbrella programme of the European Year of Intercultural Dialogue in Slovenia. It also analyses media coverage of intercultural dialogue in three national electronic and print media. The sample covers the period of the Slovenian Presidency of the Council of the EU. The starting point is that the Slovenian Presidency provided a unique opportunity for Slovenia and Slovenian news media to take the initiative in raising awareness of the importance of intercultural dialogue for fostering the ethics of intercultural and inter-ethnic cohabitation in Europe. The study's theoretical framework borrows from the cultural theory and social theory of Europeanisation. The research question is framed by two key concepts, brand (and branding) as well as the politics of identity. The study is placed within the debate on the power of intercultural dialogue to help in the democratisation and pluralisation of the politics of identity and belonging in contemporary Europe.
Keywords: European Union; Evropska unija; Intercultural relations; Medkulturni odnosi; Kulturna identiteta; Cultural identity; Mass media; Množični mediji; Slovenia; Slovenija; kulturne študije; medkulturni dialog; mediji; communication medium; identiteta